Impact of Path Characteristics and Scheduling Policies on MPTCP Performance - Arzani, Behnaz; Gurney, Alexander; Chang, Shoutian; Guerin, Roch; Loo, Boon Thau (Advanced Information Networking and Applications Workshops (WAINA), 2014 28th International Conference on, 2014)
Impact of Path Characteristics and Scheduling Policies on MPTCP Performance Behnaz Arzani, Alexander Gurney, Shoutian Cheng, Roch Guerin, Boon Thau Loo. International conference on Advanced Information Networking and Applications Workshops (WAINA), 2014 Abstract With increasing deployment of Multipath TCP (MPTCP) in multihoming and data enter scenarios, there is a need to understand how its performance is affected in practice-both by traditional factors such as RTT measurements, and by new multipath-specific considerations such as sub flow selection. We carried out an initial but comprehensive study using an actual MPTCP implementation in an emulated network environment, to explore the impact of different factors on MPTCP throughput. We find that path selection and packet scheduling have a large effect on performance, and that merely trusting the congestion control mechanism to do the right thing is not enough. Moreover, we provide evidence that throughput can be improved by slight modifications to the send buffers and path selection components of the implementation. Important challenges in network design remain, if only to ensure that multiple suitable paths exist in a network.